Language, the Parent of Thought: Speculating with Hegel - Alibrando, Samantha Park; Fritzman, J. M.; Lomas, Sarah Marchand; Southworth, McKenzie Judith (Cosmos and History: The Journal of Natural and Social Philosophy, 2017)
We speculate with Hegel about language, critiquing interpretations of Hegel's views on language given by Jim Vernon, John McCumber, Stephen Houlgate, and Michael N. Forster, as well as defending Sophisticated Radical Whorfianism from the objections of Maria Francisca Reines and Jesse Prinz.  Prior to discussing Forster, we explicate Hegel's views on mechanical memory.  We conclude by discussing why, although thought grows up, it does not move out.